Helicobacter Pylori Infection in Texas Hispanic and Non-Hispanic White Men: Implications for Gastric Cancer Risk Disparities. (July 2017) - Long Parma, Dorothy; Muñoz, Edgar; Ogden, Susan M.; Westin, Gustavo F.; Leach, Robin J.; Thompson, Ian M.; Ramirez, Amelie G.
Chronic Helicobacter pylori ( H. pylori ) infection is a major gastric adenocarcinoma (GA) risk factor. GA disproportionately affects U.S. Hispanics compared with non-Hispanic Whites (NHWs). Since H. pylori infection studies in Hispanics are few, infection rates in Hispanic and NHW men in Bexar County were compared, and relationships with ethnicity and obesity examined. Age- and zip code-matched participants from a community-dwelling cohort were randomly selected. Sera from 284 men were analyzed by enzyme immunoassay for H. pylori antibodies. Adjusted risk ratio estimation for matched data was conducted to identify differences. Hispanics had a markedly higher prevalence of infection (30.3%) than NHWs (9.2%). Matched risk ratio (mRR) analyses revealed a strong association between H. pylori seropositivity and Hispanic ethnicity (mRR = 3.31; 95% CI [1.91, 5.73], adjusted by BMI, smoking status, and family history of cancer (mRR range = 3.28-3.89). BMI mRRs (range = 1.19-1.22) were significant in all models. In this cohort, Hispanic men had higher H. pylori infection rates than NHWs, and parallel the disproportionately higher rates of GA; obesity contributes to this higher prevalence. Future studies should address country of origin, acculturation, and other factors influencing obesity to further elucidate risk of GA in Hispanic populations.